Implementation Of Buy Back Guarantee By The Bank Against The Developer As A Guarantee For Completion Bad Credit Problems - Radityo, Mochammad Erwin; Asmuni, Asmuni; Harahap, Arifuddin Muda (Faculty of Law, Universitas Pekalongan, 2024)
Purchase Back Guarantee is an agreement made by the bank and developer to provide collateral for the mortgage to the developer. Article 8 Paragraph (1) of Law Number 7 of 1992 concerning Banking as Amended by Law Number 10 of 1998 (Banking Law) stipulates that bank credit distribution must be based on confidence in the debtor, which in the provisions explaining this confidence refers to the existence of credit guarantee. In addition, Article 11 of the Banking Law regulates the provisions for providing guarantees by Bank Indonesia. However, these articles do not further regulate the collateral that can be provided for bank credit. This shows that this regulation is still rigid and many problems arise due to the implementation and execution of the Buy Back Guarantee. The aim of this study is to examine and analyze the validity of the implementation of the Buy Back Guarantee and efforts to resolve disputes. This study uses normative legal research methods with a legislative and decision approach. The study results show that the implementation of the Buy Back Guarantee is valid if it is carried out in accordance with applicable regulations and the agreements made relating to the implementation of the Buy Back Guarantee are valid and made before a Notary. Dispute resolution can be done through litigation and non-litigation. Litigation can be taken through the courts, and non-litigation can be done through Alternative Dispute Resolution, namely arbitration, negotiation or mediation.